Using Different Surfactants to Increase Oil Recovery of Rumaila Field (Experimental Work) - Salih, Talib A.; Sahi, Safaa Hussain; AL-Dujaili, Ahmed Noori Ghani (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
Enhanced oil recovery is used in many mature oil reservoirs to increase the oil recovery factor. Surfactant flooding has recently gained interest again. To create micro emulsions at the interface between crude oil and water, surfactant flooding is the injection of surfactants (and co-surfactants) into the reservoir, thus achieving very low interfacial tension, which consequently assists mobilize the trapped oil. In this study a flooding system, which has been manufactured and described at high pressure. The flooding processes included oil, water and surfactants. 15 core holders has been prepared at first stage of the experiment and filled with washed sand grains 80-500 mm and then packing the sand to obtain sand packs samples for experiment. It was found that the best rate for water injection was 1.2 PV. Productively, while the optimum injection rate was 1.0 PV economically. The study observed that the cost of water injection in secondary recovery increased 700% when PV injected increased from 1.0 PV to 8.0 PV, while the recovery increased only about 8% (58.77 – 66.7%). The effects of concentration, salinity and temperature is also explored by examined many values of each parameter according to surface tension by using capillary rise method. It was found that the optimum conditions for surfactant flooding for sodium dodecyl sulfate (SDS) 0.01 molar for concentration, 5500 P.P.M for salinity and 70 °C for temperatures. These conditions was used to all kinds of surfactants that have been used in this study. The study results indicated that the best surfactant in both productively and economically was SDS with maximum recovery about 90% for each secondary and tertiary recovery and the optimum injection volume for all surfactants 1.2 PV . Another 12 Core holders with fixed pore volume were prepared for the second stage of the experiment. At this stage the pore volume was approximately constant and the variation included different values of SDS concentrations (0.1 and 0.001 Molar) and different values of salinity (1000 P.P.M and 3000 P.P.M) and temperature equal to 90 °C. Each value for concentration was experimented with the two values of salinity which in result obtaining four flooding conditions. Each condition was flooded by three injection rates (50, 120, 200 %). The results proved the results obtained from the first stage.